STRATEGI PENANGGULANGAN KEMISKINAN: PENDEKATAN TINDAKAN KOLEKTIF (COLLECTIVE ACTION) PADA PETANI DI DESA TRETES KECAMATAN PUJON KABUPATEN MALANG - Henny Oktavianti; Munawar Ismail; Ahmad Erani Yustika (MediaTrend, 2010)
Poverty have multidimensional character. Poverty not only concern with economic, but also non-economic (social, culture and politics). One of the communities which in poverty trap is peasant. This thesis describes why peasants get poverty and what the effort of peasant to move out from poverty. Researcher observe peasant life pattern from social capital side which owned by peasant in Tretes Village. Result of this research show that social capital of peasant in Tretes Village can motivate collective action. The kinds of collective action poured into arrangement that have been done by peasant to move out from poverty trap but there are many constrains inside. Therefore, it is made compulsory indirectly governmental interference to support peasant arrangement become an action that able to move out peasant from poverty trap in Tretes Village.